Caminhos invisíveis: análise de percursos cotidianos de pessoas com deficiência visual em Fortaleza - Morano, Raquel Pessoa (2018)
The current research investigates how People with Visual Impairment (PwVI) understand, relate and move around in the city and analyze, in loco, the accessibility of traversed paths, in accordance with the Current Regulations and by the speeches of participants in order to meet their needs, limitations and abilities, as well as understand the perceptions that they have of the space and how the environment can interfere with and influence in their orientation and mobility. As field methodology, it proposes to accompany people with visual impairment in their daily routes and in scheduled routes, but first, primary and secondary data are compiled and spacealized with Geoprocessing (PEREIRA; SILVA 2001), in order to trace an overview of the situation and location of PwVI in Fortaleza. The analysis of the routes is based on a set of empirical and qualitative methodologies: Use of Questionnaires (MARCONI; LAKATOS, 1999; RHEINGANTZ, 2009); Discussed routes (THIBAUD, 2001), Semi structured Interviews (LÜDKE; ANDRÉ, 1986; LAKATOS, 1996; BONI; QUAREMAS, 2005; RHEINGANTZ, 2009; MARCONI; LAKATOS, 2012) and the use of checklist produced by the author for the analysis of the physical situation of the routes. Through this research, is expected to show the routes traversed by people with active visual disabilities, to understand how they overcome the barriers found in these routes and get to know the real situation of these physical spaces where the PwVI circulate in the city in order to receive subsidies to contribute to the consistent and effective targeting of inclusive public policies.